Investigative and Prosecutorial Strategies for Mitigating Pathways to Radicalization: Creation of a Federal Terrorism Court Record Repository, (United States), 1978-2019 - Gruenewald, Jeff ([Verlag nicht ermittelbar], 2022)
The purpose of this project was to utilize the American Terrorism Study (ATS) database to create a web portal known as the ATS Court Records Repository (ATSCoRR), which would allow intelligence analysts, federal prosecutors, Federal Bureau of Investigation (FBI) agents, state fusion centers, and NIJ-funded researchers examining radicalization in the U.S. to have access to the ATS's court records. The ATS includes federal court documents collected since 1987 relating to cases where individuals were indicted for "terrorism or terrorism-related activities" as designated by the FBI. Major variables include date of indictment, federal court district, ideological category, category of offense(s), and results of the case.